Desenvolvimento de Nanogéis Contendo Curcumina e Óleo Essencial da espécie Pectis brevipedunculata (Asteraceae) como Terapia Combinada para o controle de Aedes aegypti e Leishmaniose - MARQUES, Estela Mesquita (2025)
Transient diseases such as cutaneous leishmaniasis (TL), dengue, Zika virus and Chikungunya, transmitted by mosquitoes, represent significant challenges to public health worldwide, especially in tropical and subtropical regions. TL, a parasitic infection caused by protozoa of the genus Leishmania, affects the skin and mucous membranes, causing severe and debilitating lesions. At the same time, the rapid spread and adaptation of viruses such as dengue, Zika and Chikungunya highlight the need to develop products and methods that allow the control, treatment and, in some cases, eradication of these diseases. Thus, considering the growing resistance to conventional treatments and the high cost of drugs currently available for the treatment of these diseases, and also considering the possibility of adverse side effects, products based on natural compounds emerge as a promising alternative to traditional methods of control and treatment. The essential oil of Pectis brevipedunculata (Gardner) Sch.Bip. (OEPb), popularly known as lemongrass, has stood out as a natural alternative with larvicidal potential, especially in the control of vectors such as Aedes aegypti, due to its chemical composition, rich in oxygenated monoterpenes such as geranial and neral, with significant biological activity, offering a sustainable approach with low environmental impact compared to traditional vector control methods. In this work, an ecological nanogel based on pluronic polymers F127 and carbopol 974P of OEPb (nGP) was developed using a low-cost methodology free of organic solvents. The nGP showed good physical and chemical stability through accelerated stability tests. Characterization techniques (UV-Vis, FTIR, DLS, SEM and AFM) confirmed the incorporation of OEPb in the nGP matrix, revealing particle size in the nanometric scale. In vitro assays against A. aegypti larvae were performed and revealed that, at a dose of 500 μg/mL of nGP, mortality rates were 96.0% ± 7.0 after 24 h and 100.0% ± 0.0 after 48 h. The positive control group treated with temephos (100.0 μg/mL) achieved 100% mortality at both time points, validating the experimental conditions and providing a reference to evaluate the efficacy of the proposed product. The in vitro leishmanicidal activity was evaluated in Leishmania amazonensis promastigotes, and the in vivo anti-inflammatory effects were assessed using a mouse paw edema model. In vitro, nGF4 (EOPb-loaded nanogel) demonstrated significant leishmanicidal activity, with promastigote mortality rates exceeding 80% at 24 h and 90% at 48 h. In vivo, nGF2, nGF3, and nGF4 exhibited anti-inflammatory effects, with nGF3 and nGF4 reducing edema by 62.7% at 2 h post-treatment. The empty nanogel (nGF0) showed minimal anti-inflammatory activity. In this study, a second nanogel (nGPC) was also developed with the incorporation of two active ingredients: OEPb and curcumin, from the optimization of the nGP formulation. nGPC showed good physical and chemical stability through accelerated stability tests. Characterization techniques (FTIR, DLS, SEM, AFM, and Rheology) confirmed the incorporation of OEPb into the nGPC matrix, revealing particle size in the nanometric scale. In vitro assays against Leishmania (Leishmania) amazonensis were also performed for nGPC, and for the pure active ingredients: OEPb and curcumin. The results demonstrated that nGPC significantly increased the antipromastigote activity compared to free curcumin and OEPb. At the highest concentration tested (17.5 μg/mL OEPb and 50.0 μg/mL Curcumin, nGPC induced more than 88% mortality in LLa promastigotes over 24, 48 and 72 h, showing sustained efficacy. Even at lower concentrations, nGPC has dose-dependent activity, providing a synergistic effect between Curcumin and OEPb. These results highlight the potential of nGP and nGPC as an innovative nanocarrier for alternative treatment against leishmaniasis itself.